e-Government Maturity Model Based on Systematic Review and Meta-Ethnography Approach (Jurnal Bina Praja, 2016)
Maturity model based on e-Government portal has been developed by a number of researchers both individually and institutionally, but still scattered in various journals and conference articles and can be said to have a different focus with each other, both in terms of stages and features. The aim of this research is conducting a study to integrate a number of maturity models existing today in order to build generic maturity model based on e-Government portal. The method used in this study is Systematic Review with meta-ethnography qualitative approach. Meta-ethnography, which is part of Systematic Review method, is a technique to perform data integration to obtain theories and concepts with a new level of understanding that is deeper and thorough. The result obtained is a maturity model based on e-Government portal that consists of 7 (seven) stages, namely web presence, interaction, transaction, vertical integration, horizontal integration, full integration, and open participation. These seven stages are synthesized from the 111 key concepts related to 25 studies of maturity model based e-Government portal. The maturity model resulted is more comprehensive and generic because it is an integration of models (best practices) that exists today.